The Effect Of Solvency And Profitability On Stock Returns In Mining Sector Companies Listed On The Indonesian Stock Exchange - Amalia Reviska Selamanda; Anwar; Nurman; Anwar Ramli; Annisa Paramaswary Aslam (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
: This study examines the effect of solvency and profitability on stock returns among mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The mining industry represents one of Indonesia’s most volatile economic sectors, influenced by fluctuations in global commodity prices, energy transition pressures, and post-pandemic market uncertainty. Understanding how internal financial indicators shape investor responses within this environment is therefore essential. The study employs an associative quantitative approach using panel data regression. Solvency is measured through the Debt to Equity Ratio (DER), profitability through Return on Equity (ROE), and stock return serves as the dependent variable. A purposive sampling technique was applied, producing a final sample of 12 companies with 60 observations. Data analysis was conducted using EViews, and diagnostic procedures included normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that, individually, neither DER (p = 0.7295) nor ROE (p = 0.2456) has a significant effect on stock returns. However, when tested simultaneously, DER and ROE significantly influence stock returns, as indicated by the F-statistic probability value of 0.0142. The Adjusted R² value of 0.2373 demonstrates that the two variables jointly explain 23.73 per cent of stock return variation, while the remaining 76.27 per cent is determined by other factors not included in the model. These findings suggest that solvency and profitability do not independently drive investor reactions in a highly volatile sector; however, taken together, they form an important component of market valuation, particularly under conditions of uncertainty and fluctuating industry performance.